Synthesis and microstructural characterization of a novel multicomponent equiatomic ZrNbAlTiV high entropy alloy. (November 2016) - Vishwanadh, B.; Sarkar, N.; Gangil, S.; Singh, S.; Tewari, R.; Dey, G.K.; Banerjee, S.
Abstract: A high entropy alloy containing ZrNbAlTiV in equiatomic ratio was produced by suction casting technique. Cross-sectional microstructure showed equiaxed morphology at the peripheral and dendrite morphology at the center region of the sample. Electron microscopic analysis revealed that the single phase and the dendrite phase have ordered bcc structure and the inter-dendrite phase has hexagonal structure. Compositions of the single phase and dendrites were same as that of the alloy composition, whereas, edges of dendrite and inter-dendrite regions show preferential partitioning of Nb and Zr respectively. These results have been rationalized in terms of cooling rates and interactions among elements. Abstract : Graphical abstract